2021
DOI: 10.3390/ijerph18168296
|View full text |Cite
|
Sign up to set email alerts
|

Suicide-Related Knowledge and Attitudes among a Sample of Mental Health Professionals

Abstract: Inadequate knowledge of the potential signs and risk factors of suicide negatively affects the ability of healthcare professionals to recognize patients at risk of suicide. The principal aim of the present study is to assess the attitudes and knowledge about suicide in a large sample of mental health professionals. We examined the relationship between Suicide Knowledge and Skills Questionnaire items and the experience of a patient dying by suicide. We also examined whether various healthcare professionals resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…4 Training on mental health have improved attitudes of health professionals' attitudes towards mental illnesses and suicide prevention. [5][6][7] These effects could be attributable to the impact of training, knowledge, academics, culture, societal background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Training on mental health have improved attitudes of health professionals' attitudes towards mental illnesses and suicide prevention. [5][6][7] These effects could be attributable to the impact of training, knowledge, academics, culture, societal background.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Improving literacy on mental health, decreasing stigma, utilizing the knowledge base to change attitude and behavior, early recognition, appropriate referral in time to bridge the mental health gap is a high priority need of current times to deal efficiently the huge burden of mental health problems affecting lives from all spheres. [4][5][6][7] Widespread misinformation, myths, stigma, lack of knowledge, resource constraints all are causing treatment barriers. Literacy of suicide can be one important dimension to be improved bringing out changes in attitudes, behavior, stigma reduction ultimately empowering the suicide reduction campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Also, 69.3% of the nurses stated that they had not received information on intervention in patients at risk of suicide. The researchers reported that between 44% and 84.5% of nurses had not received information on intervention in patients at risk of suicide (Erbuto et al, 2021; Fry et al, 2019; Ramberg et al, 2016). One study revealed that nurses were forced to plan their own strategies to manage patients at risk of suicide, because they had received no training (Marutani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, improved knowledge and attitudes about suicide risk may allow ECPs and trainees to better identify patients with suicidal ideation and suicidal attempts, increasing suicide-prevention strategies. To our knowledge, only a few papers investigated knowledge and attitudes toward suicide among mental health professionals [ 17 , 18 ]. Jiao et al compared knowledge and attitudes toward suicide in a sample of 187 psychiatrists from different psychiatric hospitals in Shanghai versus 548 urban community members [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that psychiatrists presented more stigmatizing beliefs about suicide, although they considered suicide an important social concern. Furthermore, Erbuto and coworkers demonstrated that healthcare professionals, who reported a patient’s suicide, had more suicide skills and an increased tendency to hospitalize suicide-risk patients in a psychiatric unit than professionals who had not reported a patient’s suicide [ 18 ].…”
Section: Introductionmentioning
confidence: 99%